Evaluating the Impact of Reality Therapy on Temperament and Sleep Quality in Adolescents with Learning Disorders: A Randomized Controlled Trial - Hayes, Ethan (Psychological Research in Individuals with Exceptional Needs, 2024)
The primary objective of this study was to evaluate the effectiveness of Reality Therapy in improving temperament and sleep quality among adolescents with learning disorders. This randomized controlled trial included 30 adolescents, aged 12 to 18, diagnosed with learning disorders. Participants were randomly assigned to either the intervention group (15 participants) or the control group (15 participants). The intervention group underwent twelve 60-minute sessions of Reality Therapy over a two-month period, while the control group received no therapeutic intervention. Temperament and sleep quality were assessed using the Revised Dimensions of Temperament Survey (DOTS-R) and the Pittsburgh Sleep Quality Index (PSQI), respectively, at three time points: pre-intervention, post-intervention, and two-month follow-up. Data were analyzed using analysis of variance (ANOVA) with repeated measurements and the Bonferroni post-hoc test, with SPSS-27 software. The results indicated significant improvements in both temperament and sleep quality in the intervention group compared to the control group. These improvements were sustained at the two-month follow-up. Specifically, the intervention group showed marked improvements in emotional regulation and sleep patterns, highlighting the efficacy of Reality Therapy in addressing these critical aspects of adolescent health. Assumptions for ANOVA were confirmed, ensuring the robustness of the findings. Reality Therapy significantly improves temperament and sleep quality in adolescents with learning disorders, with effects lasting beyond the intervention period. This study supports the use of Reality Therapy as a viable intervention for improving emotional and sleep-related outcomes in this population. Further research with larger sample sizes and extended follow-up periods is recommended to confirm these findings and explore additional benefits.